Door of the Federal Reserve Bank of Boston at 30 Pearl Street, July 30, 1975 - Unknown (Tufts Archival Research Center, 2005)
Detail of the main door at the Federal Reserve Bank of Boston, located at 30 Pearl Street. The door is located at the northwest corner of the building. 4 7/8 x 3 1/2 Photographs